Corporate governance and firm cash holdings in Malaysia - Azira Hanani, Ab. Rahman (Universiti Malaysia Sarawak (UNIMAS), 2011)
ThiS study observed data for 512 public listed companies in Malaysia" to find the relationship between cash holdings and corporate govema~ce. Using data from Data Stream and firms' annual reports for the financial year 2009, this study found that only Board Independence has positive relationships with cash holdings. Meanwhile, there are insignificant relationships -between cash holdings and Board Size as well as CEO DualitVThis study also examined the relationship of cash holding with finn size, capital expenditure, cash flow, leverage, dividend, Market to Book and working capital. 5 out of 7 control variables show significant relationship. From the study, it is found that cash holdings have positive relationship with cash flow ratio, dividend, leverage ratio, market to book ratio and working capital ratio.